0971 Methods and Schedule-Related Differences in a Multi-center Trial of Rapidly Cycling versus Extended Duration Work Rosters. (12th April 2019) - Stone, Katie L; Landrigan, Christopher P; Blackwell, Terri; Rahman, Shadab A; Kriesel, Dana R; Vittinghoff, Eric; O'Brien, Conor S; Sullivan, Jason P; Viyaran, Natalie C; Lockley, Steven W; Barger, Laura K; Wright, Kenneth P; et al.
Abstract: Introduction: Extended duration work shifts in resident-physicians may impact safety and performance, but the relative benefits and harms of eliminating extended duration shifts is uncertain. Methods: We conducted a multi-center, cluster-randomized crossover trial in pediatric Intensive Care Units (ICUs) at 6 academic medical centers to compare two schedules among residents: an extended duration work roster (EDWR) that included some shifts of 24 hours or longer, and a rapidly cycling work roster (RCWR) which eliminated longer shifts. Schedule order was randomly assigned. Patient safety outcomes were tracked by centrally trained physician observers and chart review, and were centrally adjudicated. Resident-related outcomes included sleep and work (based on diaries and actigraphy), alertness (psychomotor vigilance task), and questionnaire-based data on mood, health and resident experience. Patient census data and average number of resident-physicians present daily across the months of data collection at each site were used to assess workload, expressed as average number of ICU patients per resident-physician (IPRP). Results: A total of 210 and 203 resident rotations (residency program Years 2 and 3) were assigned to RCWR and EDWR, respectively. Compared to residents who refused participation (13 in RCWR; 6 in EDWR), those who participated were more likely to be in residency program Year 3 (p=.03); all other baseline characteristics including age, gender, race/ethnicity, and medical specialty were similar (p>.05). Overall baseline characteristics of both residents and patients were similar between the two schedules (p>.05 for all comparisons). An unanticipated significant difference in resident workload on the two schedules was observed, with mean IPRP of 8.52 on RCWR vs 6.86 on EDWR (p<.001). Significant site-level variations in IPRP were also observed, with estimates ranging from 4.1 to 10.0 patients per resident-physician on EDWR, and from 5.0 to 13.0 on RCWR. Conclusion: We successfully completed a multi-center trial to assess the impact of varying resident work schedules on patient safety and other outcomes. Future studies should carefully consider the impact of schedule changes on resident workload. Support (If Any): NHLBI U01-HL-111478, U01-HL-111691, and the ROSTERS Study Group.